Exploring duration gap of Islamic banks during COVID-19 crisis: an inter-regional online focus group study. (31st August 2022) - Shah, Syed Alamdar Ali; Fianto, Bayu Arie; Herianingrum, Sri; Sukmana, Raditya
This study explores the duration gap risk management of Islamic banks during the COVID-19 crisis using online focus group studies. There are 12 participants from Indonesia, Malaysia, Pakistan and UAE. Findings suggest that COVID-19 has increased the duration gaps of Islamic banks. The causes include, lack of business opportunities, relaxations in terms of policy rates, restructuring offered by central banks and attitudes of the customers of Islamic banks to avail relaxations offered, whether they need it or not. Finally, the crisis has exhibited that customers have managed their spending according to conventional theories of demands of money and Maslow's hierarchy of needs.